Draft genome sequence of Acinetobacter haemolyticus strain MUWRP1017 isolated from the pus of a female inpatient at Bwera General Hospital in Uganda - Wokorach, Godfrey; Erima, Bernard; Alafi, Stephen; Kabatesi, Hope O; Muhindo, Julius T; Najjuka, Florence; Kiyengo, James; Kibuuka, Hannah; Musinguzi, Ambrose K.; Wabwire-Mangen, Fred; Byarugaba, Denis K. (American Society for Microbiology, 2024)
The bacterium Acinetobacter haemolyticus, with a genome size of 3.4 Mb, was isolated from a pus swab of a wound on the left lower limb above the ankle joint of a female patient. This strain carries the antimicrobial resistance genes cephalosporinase blaADC-25, oxallinase blaOXA-264, floR, and sul2 and other resistance and virulence genes.